2012
DOI: 10.1126/science.1217745
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Driving Energy and Delocalized States for Charge Separation in Organic Semiconductors

Abstract: The electron-hole pair created via photon absorption in organic photoconversion systems must overcome the Coulomb attraction to achieve long-range charge separation. We show that this process is facilitated through the formation of excited, delocalized band states. In our experiments on organic photovoltaic cells, these states were accessed for a short time (<1 picosecond) via infrared (IR) optical excitation of electron-hole pairs bound at the heterojunction. Atomistic modeling showed that the IR photons prom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

58
1,380
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,101 publications
(1,442 citation statements)
references
References 48 publications
58
1,380
4
Order By: Relevance
“…122 In the PPP technique, a working device is first pumped by visible light, creating separated charges and/or localised CT states. The pump excitation is followed by an infrared push pulse, which is supposed to re-excite the localised CT states into separated charges.…”
Section: The Role Of Charge Delocalisation On Free Charge Generationmentioning
confidence: 99%
“…122 In the PPP technique, a working device is first pumped by visible light, creating separated charges and/or localised CT states. The pump excitation is followed by an infrared push pulse, which is supposed to re-excite the localised CT states into separated charges.…”
Section: The Role Of Charge Delocalisation On Free Charge Generationmentioning
confidence: 99%
“…C harge separation has a key role in determining solar energy conversion efficiency of semiconductor-based systems for producing solar electricity and solar fuels through solar cells [1][2][3][4] , photoelectrocatalysis [5][6][7][8] and photocatalysis [9][10][11][12][13] . As a key step in energy conversion, electron-hole pairs generated by light absorption need to be separated and transferred to the surface of the semiconductors 1,9,[14][15][16][17] .…”
mentioning
confidence: 99%
“…Thus, certain facets of a semiconductor prefer reduction while others favour oxidation [18][19][20] . However, reports on the reduction and oxidation reaction facets on the same semiconductor crystal (such as TiO 2 ) were often contradictory in the literature [21][22][23][24][25][26] . For example, it was reported that rutile {011} and anatase {001} faces provided the sites for oxidation, while the rutile {110} and anatase {101} faces offered the sites for reduction 24 .…”
mentioning
confidence: 99%
“…Light absorption by the polymer has been largely improved towards the near infrared (NIR) spectral region by the introduction of low-bandgap co-polymers 4,5 . Exciton dissociation, however, remains to be understood and has recently been the subject of several investigations [6][7][8][9][10] .…”
mentioning
confidence: 99%
“…There, the large energy offset (  0.5 eV) between the lowest unoccupied molecular orbitals (LUMOs) of polymer and fullerene, possibly gated by the formation of hot delocalized states 9 , drives exciton dissociation and charge separation. This is supposed to occur only after diffusion of the excitons in the polymer, which is usually forming an interpenetrating network of domains with the fullerene 12 .…”
mentioning
confidence: 99%